Monoclonal antibodies directed to the erbB-2 receptor inhibit in vivo tumour cell growth. - Harwerth, I. M. (Nature Publishing Group, 1993)
Four monoclonal antibodies (MAbs) specific for the extracellular domain of the human erbB-2/HER2 protein (FRP5, FSP16, FWP51 and FSP77) have been isolated (Harwerth et al., J. Biol. Chem., 267, 15160-15167, 1992). In this paper we describe the effects of erbB-2 specific MAb administration on the tumorigenic growth of human erbB-2 transformed NIH3T3 cells implanted into athymic nude mice. Two antibodies, FWP51 and FSP77, inhibited the onset of tumour growth, while the administration of FRP5 and FSP16 did not affect tumour growth. In addition, administration of MAbs FWP51 and FSP77 led to a retardation in the growth of established tumours. Treatment was not curative in that tumours regrew within two weeks of the final treatment. The administration of a combination of MAbs FWP51 and FSP77 which react with two distinct regions on the erbB-2 molecule was more effective than treatment with either MAb alone. The two growth-inhibitory antibodies were also effective in the treatment of tumours established from SKOV3 cells, a human ovarian tumour cell line with high levels of the erbB-2 protein. The effect of the MAbs on the anchorage-independent growth of erbB-2 transformed cells and on erbB-2 receptor turnover was also measured. IMAGES: